Beyond Scarcity: Transformational Leadership and Resource Bricolage in Navigating Geographical and Structural Barriers in an Indonesian Madrasah - Anisa Muthiatul Husnah Maksum; Abdullayeva Muhlisa (Sustainable Human Capital Development Journal, 2026)
This study examines how transformational leadership addresses structural and geographical barriers in an Indonesian madrasah. The research focuses on MAN 2 Gresik, a school facing severe challenges related to chronic clean-water scarcity and regulatory constraints in accessing government infrastructure funding. Despite these limitations, the institution achieved remarkable academic and organizational performance, raising questions about the role of leadership in transforming institutional constraints into strategic advantages. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis of institutional achievements from 2021 to 2025. The findings reveal that transformational leadership was operationalized through adaptive and innovative strategies aligned with the dimensions of inspirational motivation, intellectual stimulation, idealized influence, and individualized consideration. Key strategies included transforming a water crisis and failed drilling attempts into a school-based business unit, “Mandagres Mineral,” as well as resolving land-ownership barriers to secure government funding through SBSN schemes. In addition, digital leadership initiatives and performance-based recognition systems strengthened institutional resilience and human capital development. The study demonstrates that transformational leadership functions as a form of “resource bricolage,” in which leaders creatively reconfigure limited resources and institutional constraints into organizational strengths. This research contributes to educational leadership literature by providing a practical framework for educational institutions operating in geographically and structurally constrained environments